The Role of Innovation Orientation in Improving Marketing Communication and Marketing Performance of Micro, Small, and Medium Enterprises (MSMEs) in the Culinary Sector - Ratna Dewi; Rahmad Solling Hamid; Andi Sismar; Riska Eka Putri Bachtiar; Sudarman Moonai; Asriany (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
This research aims to understand how aspects of innovation orientation influence marketing communication strategies and ultimately contribute to the marketing performance of women entrepreneurs. The empirical analysis was conducted using a sample of 120 entrepreneurs in micro, small, and medium enterprises in the culinary sector. This study used an online survey for data collection. After passing reliability and validity tests, the data were analyzed with partial least squares structural equation modeling. The research results indicate that innovation orientation has a significant positive direct influence on marketing communication. Innovation orientation also has a significant direct positive influence on marketing performance. Furthermore, self-motivation has a significant positive direct influence on marketing performance. Finally, marketing communication also has a significant positive influence on marketing performance.